Utilization of rehabilitation services among older adults with physical disabilities: the interactive influence of regional development and socioeconomic position - Wang, Yi-Ran; Yan, Xiao-Qian; Zhang, Fan; Zhang, Chen-Tao; Liang, Wan-Nian (Frontiers in Public Health, 2025)
BackgroundThe utilization of rehabilitation services by older adults with disabilities is an important health task in the context of population aging and disability expansion. This study aims to explore whether there are structural differences in the relationship between the socioeconomic position (SEP) of older adults with physical disabilities (PD) and their utilization of rehabilitation services across urban and rural areas.MethodsA total of 19,782 observations of older adults with PD from the 2007–2013 China National Survey on Disability and the 2006 Second National Sample Survey on Disability were included in this study. This study employs a multiplicative interaction effect model based on logistic regression to analyze the differential impact of individual SEP on the utilization of rehabilitation services among urban and rural older adults with PD.ResultsThe results indicate that higher annual per capita household income has a stronger influence on the utilization of rehabilitation services in urban areas (OR = 1.315, 95% CI 1.028–1.683). This may be due to the higher development level in urban areas, which amplifies the positive effects of high SEP on individual health investments. Conversely, individuals with lower SEP in urban areas may experience “self-limiting” behavior and difficulties in integrating into the urban and social welfare systems, further inhibiting the utilization of rehabilitation services.ConclusionThere is a structural urban–rural difference in the relationship between SEP and the utilization of rehabilitation services among older adults with PD. It is recommended to enhance both the accessibility and affordability of rehabilitation services for disadvantaged individuals in economically advantaged regions, while in economically disadvantaged regions, efforts should focus on improving the accessibility of rehabilitation infrastructure and strengthening the affordability of services for vulnerable populations. This can be achieved through legislative safeguards, financial assistance, and the development of a coordinated service delivery system.